Repositioning Religious Organization Activism in The Digital Era - Tijani, Ach; Banyal, Abdul Muin (Al-Albab, 2024)
The rise of the digital world poses a challenge to the position of religious organizations. This is evident in the emergence of new authorities, both individuals and groups, outside traditional religious structures. Nahdlatul Ulama (NU), a mainstream traditional organization, has also been impacted by this shift. However, several studies indicate that NU has effectively adapted to various challenges and situations over time. This analysis focuses on how NU, as a representative of traditional mainstream Islamic organizations, has repositioned itself in response to the digital era, using the example of its activities in Mojokerto. This work addresses two key issues: first, how NU adapts to the presence of social media; second, what strategies NU employs to reposition itself in the face of these new challenges on social media. To explore these questions, this work employs a qualitative methodology, collecting data through interviews, observations, and documentation. The data is then analyzed and presented using a digital religion approach. The findings suggest that NU has repositioned itself in two main ways. First, through adaptation, by adopting and actively using social media platforms such as Facebook, Instagram, and YouTube via the organization’s official accounts. Second, through a form of resistance, by having NU activists engage on social media without prominently displaying their organizational affiliation.